Cytotoxicity of Fumaria Officinalis on Leishmania Tropica, L20B Cell Lines and Bacteria In Vitro - Ahmed Younus Abed (Journal of Global Pharma Technology, 2016)
Fumaria officinal is (Shahatraja in Arabic), one of the popular herbal medicines used in Iraq. There are more than 60 species of Fumaria around the world, and many useful properties recognized for this herb. The aim of this study is to investigate the effects of the extracted alkaloids, and crude alcoholic extract on Leishmania tropica (L tropica), and L20B cancer cell lines, in additional to study the toxic effect of these two extracts on many types of bacteria and comparing the results in both cases. Viability rate of treating L tropica cells by the alkaloids and crude extracts were increased significantly in all concentrations. All concentrations of alkaloids extract showed toxic effect on L20B cell lines, except (0.015 mg/ml). While for crude extracts, there was no effect on Viability rates of L20B cell lines at all concentration, except (0.125 mg/ml), shown some decrease in Viability rate. The antibacterial activities of the alkaloids increased comparing with crude extracts in four strains of bacteria, Staphylococcus aureus, Bacillus spp., Klebsiella spp., and Proteus spp. While for Salmonella spp., the inhibition zone was increased in crude extracts more than alkaloids. The results for three remaining bacteria (Streptococcus pyogenes, E. coli, and Enterobacter spp.) were equal in their inhibition activity. From results of present study, the alkaloids that extract from Fumaria officinalis, made the best effect as anticancer and antibacterial agent.Keywords: Cytotoxicity, Anticancer activity, alkaloids, Fumaria officinalis, L20B cell line, antibacterial agent.